1997
DOI: 10.1038/sj.onc.1200906
|View full text |Cite
|
Sign up to set email alerts
|

The RIα subunit of protein kinase A (PKA) binds to Grb2 and allows PKA interaction with the activated EGF-Receptor

Abstract: Functional interactions between protein kinase A (PKA) and epidermal growth factor receptor (EGF-R) signalling pathways have been suggested. Unlike the type II isoform of PKA (PKAII), the type I (PKAI) and/or its regulatory subunit RIa are generally overexpressed in cancer cells and are induced following transforming growth factor a (TGFa)/EGF-R-dependent transformation. Downregulation of RIa/PKAI inhibits TGFa expression and EGF-R-dependent signalling. We have previously shown that addition of EGF to quiescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 14 publications
0
57
0
Order By: Relevance
“…This result suggests, therefore, that although the two Ret versions display a di erent cellular localization, they show the same interaction with Grb2-SH2 domain. The weak, but reproducible binding to Grb2 of the receptorial version of Ret iso9 protein indicates that the binding between Grb2 and Ret/ptc2 could not be due to its 5' end-RIa derived sequence, as it could be hypothesized following a recent report about Grb2-RIa protein interaction (Tortora et al, 1997), but instead it should be attributed to an interaction with the C-terminus of Ret protein itself.…”
Section: Resultsmentioning
confidence: 77%
“…This result suggests, therefore, that although the two Ret versions display a di erent cellular localization, they show the same interaction with Grb2-SH2 domain. The weak, but reproducible binding to Grb2 of the receptorial version of Ret iso9 protein indicates that the binding between Grb2 and Ret/ptc2 could not be due to its 5' end-RIa derived sequence, as it could be hypothesized following a recent report about Grb2-RIa protein interaction (Tortora et al, 1997), but instead it should be attributed to an interaction with the C-terminus of Ret protein itself.…”
Section: Resultsmentioning
confidence: 77%
“…Since PKA-I expression has been related to cell proliferation and transformation (Miller et al, 1993;Tortora et al, 1993;Cho-Chung et al, 1995) and 8-Cl-cAMP down-regulates the expression of RIα subunit of PKA in KB cells (Budillon et al, unpublished observation), this effect could interfere with EGFinduced signalling. In this regard, Tortora et al reported that RIα subunit binds to Gbr2 and allows the interaction of PKA-I with the activated EGF-R in human breast MCF-10 cells (Tortora et al, 1997a), suggesting a possible interference of PKA-I inhibitors with the early steps of EGF-R-mediated signalling. In our system we did not examine if this interaction is present or if it is regulated by 8-Cl-cAMP.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the RI␣-GFP fusion protein (pRI␣-GFP) accumulated in green dots at and around the NMJ in 77% of the expressing fibers. Type I PKA can be recruited by activated epidermal growth factor receptor through interaction of a proline-rich region of RI␣ (residues 82-91) with the SH3 domains of the Grb2 adapter protein (39). However, this proline stretch is not required for the accumulation of the fusion proteins because deletion of this region in pRI␣ (1-81)-GFP did not abolish localization (Figs.…”
Section: The Dimerization Domain Of Ri␣ Directs Its Accumulation At Tmentioning
confidence: 99%